The Development of Flascard Media to Teach Descriptive Text of Material on Reading Skill Class VII SMP Excellent Garum - Zulfa, Laela; Rofi'ah, Siti; Makhrifah, Istina Atul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to explore the development of flashcard media for teaching descriptive text material in reading skills to seventh-grade students at SMP Excellent Garum. Additionally, it seeks to analyze the effectiveness of flashcard learning media, as the ADDIE model provides structured and precise steps for media development (Branch, R.M., 2009). The researcher developed the flashcard media and then submitted it to material and media experts for evaluation and assessment. The validation results showed a media expert approval rating of 82.5% and a material validation score of 87.5%, categorizing it as "Highly Valid" as a supplementary learning tool. Moreover, student response results reached 81.0%, indicating that flashcard learning media is highly suitable for use.